Identification de l’avant-garde et identité de l’artiste : les femmes et le groupe automatiste au Québec (1941-1948) - Arbour, Rose (RACAR : Revue d'art canadienne / Canadian Art Review, 1994)
This essay examines the status of women artists directly or indirectly related to the Automatist Movement in Quebec during the 1940s. Some of these women were signatories of the group's notorious Refus global (1948) manifesto, which marked a turning point in radical modern thought in Quebec. The author first recontextualizes the contribution of women artists to the art vivant milieu during the inter-war years; she then discusses an important aspect of radical modernity (avant-garde) as represented by the Automatists (1942-54): the plurality of disciplines and the trans-disciplinary practice, characteristic of nearly all the women artists involved in this movement. In conclusion, she offers an analysis of the significance of the signing of the Refus global for women artists: had they not done so, most of them would not be recognized as part of the history of this artistic and literary avant-garde movement, let alone the history of art in general.This study reveals the extent to which avant-garde activity relies on theoretical thought and writing to become a part of history. That few women have made their mark in artistic avant-garde movements has been attributed, in part, to the fact that they have written little, if at all. The same would no doubt be true of the women artists discussed here had they not signed their name to the Refus global. A number of them would undoubtedly have been acclaimed even without this signatory consecration, but recognition would have come at a later date and in another context.